Prototype Sistem Peringatan Dini Kebocoran Gas LPG dan Deteksi Api Berbasis Telegram Menggunakan Esp8266 - Fachrozi Yusril (International Research on Big-Data and Computer Technology: I-Robot, 2025)
Liquefied Petroleum Gas (LPG) is a primary energy source widely used byhouseholds and small and medium enterprises (SMEs), but it carries a highpotential for danger if a leak occurs. This research aims to design and implementa prototype of an automatic LPG gas leak detection system based on an ArduinoUno equipped with an MQ-2 sensor, a flame sensor, a buzzer, an I2C LCD, andan ESP8266 module for sending notifications via Telegram. The developmentmethod used is the Waterfall model, which includes requirements analysis, systemdesign, implementation, testing, and maintenance.The system was tested at Kedai Rumalam, a culinary SME that did not yet have agas safety system. Test results demonstrated that the system was able to detect gasleaks and the presence of fire with high accuracy. The system's response wasdemonstrated by buzzer activation in less than 2 seconds and Telegramnotification delivery in approximately 5 seconds. The system was proven toprovide early warnings locally and remotely and did not generate false positivesunder normal conditions. With its low cost and ease of implementation, this systemis suitable for use in SME environments as a preventative measure against firescaused by gas leaks.